Repurposed Drugs and Alternate Therapeutic Possibilities for Challenges Posed By Covid-19 - Verma, Khushbu; Kapoor, Neha; Kumar, Lamha; Yadav, Neelam; Mondal, Ghorai Soma (Asian Journal of Pharmaceutical Research and Development, 2021)
Pandemics like SARS-CoV-2 and its associated illness named COVID-19 (coronavirus disease 2019) have become a regular occurrence in the past recent decades. Though, novel Coronavirus devastated human lives, its earlier cousins SARS-CoV1, MERS and lesser known infections like 229E, NL63, OC43, HK01 were less threatening. Humankind should brace up towards identifying, managing and finding a suitable cure to prevent incidence of such deadly diseases.it is a well-known fact that viral diseases can be curbed only with vaccines. In this respect, the world has witnessed both the design and delivery of vaccines against SARS-CoV2 in a record time. Candidates for Vaccines designed vary from targeting proteins or nucleic acids (DNA and RNA) of the virus, with or without adjuvants with a potency to generate memory. Though, this has been lauded by the entire humankind, there is still the need for other therapeutics to control and treat COVID-19. Therapeutic Drugs are inexhaustible group of molecules that showed some promise in diagnosis, treatment or prevention of SARS-CoV-2 but provide no form of ‘memory’. In this Review, we summarize the current knowledge on the therapeutic options other than vaccines or licensed antiviral drugs that can be repurposed to be considered for the treatment and prevention of the SARS-CoV-2 virus.